2024
DOI: 10.1371/journal.pone.0300883
|View full text |Cite
|
Sign up to set email alerts
|

Host microbiome depletion attenuates biofluid metabolite responses following radiation exposure

Evan L. Pannkuk,
Igor Shuryak,
Anika Kot
et al.

Abstract: Development of novel biodosimetry assays and medical countermeasures is needed to obtain a level of radiation preparedness in the event of malicious or accidental mass exposures to ionizing radiation (IR). For biodosimetry, metabolic profiling with mass spectrometry (MS) platforms has identified several small molecules in easily accessible biofluids that are promising for dose reconstruction. As our microbiome has profound effects on biofluid metabolite composition, it is of interest how variation in the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Our validated serum metabolite panel for the current TBI cohorts (16 metabolite panel) was higher than what we established for our previous VHDR studies (3 metabolite panel) (Tables 3 and 4). 30,31 The number of metabolites and their corresponding metabolic pathways are in line with other studies following IR exposure in mouse 54 and NHP models, 68 where we primarily observed changes in amino acids, energy metabolites, and lipids. Of these, lipid concentrations tended to change irrespective of shielding or total body exposure (LysoPC [14:0], [16:1], [18:1], and 18:3).…”
Section: Effects Of Partial Body Irradiation On Serum Markers Of Radi...supporting
confidence: 89%
See 4 more Smart Citations
“…Our validated serum metabolite panel for the current TBI cohorts (16 metabolite panel) was higher than what we established for our previous VHDR studies (3 metabolite panel) (Tables 3 and 4). 30,31 The number of metabolites and their corresponding metabolic pathways are in line with other studies following IR exposure in mouse 54 and NHP models, 68 where we primarily observed changes in amino acids, energy metabolites, and lipids. Of these, lipid concentrations tended to change irrespective of shielding or total body exposure (LysoPC [14:0], [16:1], [18:1], and 18:3).…”
Section: Effects Of Partial Body Irradiation On Serum Markers Of Radi...supporting
confidence: 89%
“…TML is a methylated lysine derivative that is a precursor for carnitine synthesis, which was first proposed as a radiation marker after being identified in humans undergoing radiotherapy . Increases in mouse urinary TML levels have been identified in several experiments recapitulating realistic radiation exposures. ,, It also increases at higher doses independent of impaired inflammatory pathways and in mice with depleted microbiomes …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations